Analisis Efektivitas Distribusi Zakat Produktif Dalam Meningkatkan Kesejahteraan Mustahik (Studi Kantor Cabang Rumah Zakat Sumatera Utara) - Mulkan Syah Riza (Universitas Islam Negeri Sumatera Utara, 2019)
This study aims to explain how the distribution of productive zakat in the Rumah Zakat North Sumatra and how the effectiveness of productive zakat distribution in improving the welfare of mustahik in the Rumah Zakat North Sumatra. This study uses a qualitative approach with a type of descriptive method, which is a problem that guides researchers to explore and photograph situations that will be thoroughly investigated, broadly and deeply. Data collection techniques with field research, while the tools used are observation, interviews and documentation. Data analysis used is descriptive qualitative analysis. The results of this study inform that in distributing productive zakat funds, Rumah Zakat is in accordance with Law No. 23 of 2011 concerning Management of Zakat. The distribution of productive zakat carried out by the Rumah Zakat North Sumatra through the Senyum Mandiri Program to mustahik in Medan Helvetia Subdistrict has been effective, because it can improve the welfare of mustahik, this is evidenced by the income of eight of thirteen mustahik people in total, five people whose income is fixed and four out of eight people whose income has increased has reached the level of muzaki.